Adverse Pregnancy Outcomes Among HIV-positive Women in the Era of Universal Antiretroviral Therapy Remain Elevated Compared With HIV-negative Women. Issue 9 (7th May 2021) - Tukei, Vincent J.; Hoffman, Heather J.; Greenberg, Lauren; Thabelo, Ramatlapeng; Nchephe, Masepeli; Mots'oane, Tsietso; Masitha, Matseliso; Chabela, Mammatli; Mokone, Majoalane; Mofenson, Lynne; Guay, Laura; Tiam, Appolinaire
Abstract : Background: Without treatment, HIV infection in pregnant women is associated with adverse pregnancy outcomes. We compared adverse pregnancy outcomes among HIV-positive women on antiretroviral therapy (ART) and HIV-negative women who enrolled for antenatal care in selected health facilities in Maseru district, Lesotho. Methods: We enrolled a cohort of HIV-positive and HIV-negative women at their first antenatal visit and followed them through delivery. Study data on miscarriage, stillbirth, preterm birth, low birth weight and birth defects were collected through participant interviews and medical record abstraction. We used the Rao-Scott χ 2 test and the t test to assess differences in characteristics and outcomes between HIV-positive and HIV-negative women and generalized estimating equations for multivariable analysis. Results: A total of 614 HIV-positive and 390 HIV-negative pregnant women were enrolled in the study with delivery information on 571 (93.1%) and 352 (90.3%) respectively. In the delivery cohort, the median age at enrolment was 28 years for HIV-positive women and 23 years for HIV-negative women with median gestational ages of 20 and 21 weeks, respectively. A total of 149 singleton pregnancies had documented adverse pregnancy outcomes; 33 (9.6%) HIV-negative pregnancies and 116 (20.6%) HIV-positive pregnancies. Compared with their HIV-negative counterparts, HIV-positive women were more likely to experience an adverse pregnancy outcome, adjusted odds ratio (AOR) 2.6 [95% confidence interval (CI): 1.71–3.97]; an intrauterine death (miscarriage or stillbirth), AOR 2.64 [95% CI: 1.25–5.49]; or a low birth weight delivery, AOR 1.89 [95% CI: 1.16–3.09]. Conclusion: Adverse pregnancy outcomes remained 2–3 times higher among HIV-positive women compared with HIV-negative women despite universal ART.